Perubahan koefisien stabilitas (kd) lapis lindung gamapod Akibat patah salah satu kakinya - Perpustakaan UGM, i-lib ([Yogyakarta] : Fak. Pertanian UGM, 1998)
ABSTRACT Gamapod is a symetrical four legs material used for armoring rubblemound breakwaters. Past researches indicated that the material has higher stability number than the Tetrapod Previous researches on Gamapod stability were conducted only up to 10% of breakwater damage and no broken Gamapods were considered. The inclusion of broken Gamapods, for example one of the legs is broken, certainly may reduce the overall stability number. The broken Gamapod may be resulted from low quality of Gamapod, careless installation, and due to extreme wave attack. It is of interest to investigate the stability number of Gamapod armor layer with various percentage of broken units. The results of the experiment showed that damage there are significant reduction of Gamapod stability number at 5%, 10% and 15%. At less than 10% damage there there was also a different pattern of damage curve. The damage curve become similar to that of Gamapod armor layer without broken units as the damage percentage higher than 10.